2014
DOI: 10.3109/10717544.2014.901436
|View full text |Cite
|
Sign up to set email alerts
|

Linear-dendrimer type methoxy-poly (ethylene glycol)-b-poly (ɛ-caprolactone) copolymer micelles for the delivery of curcumin

Abstract: (2015) Linear-dendrimer type methoxy-poly (ethylene glycol)-b-poly (ɛ-caprolactone) copolymer micelles for the delivery of curcumin, Drug Delivery, 22:1, 58-68, DOI: 10.3109/10717544.2014 Methods: A novel linear-dendrimer methoxy-poly (ethylene glycol)-b-poly ("-caprolactone) copolymer was synthesized through O-alkylation, basic hydrolysis and ring-opening polymerization reaction with methoxy-poly (ethylene glycol), epichlorohydrin and "-caprolactone as raw materials. Its structure was characterized by 1 H-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 48 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…The curcumin-loaded NPs (Cur-NPs) of small size were obtained from the copolymer’s self-assembling aided by thin-film hydration with effective encapsulation. 10 Our results demonstrated that Cur-NPs can significantly raise dissolution ratio of curcumins in water, providing a proper sustained-release characteristic for curcumin in vitro, suggesting that the Cur-NP is an appropriate candidate for the continuous delivery of curcumin. In the current study, we further evaluated the anti-atherosclerotic function of this Cur-NPs in apolipoprotein E −/− mice (apoE −/− mice).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The curcumin-loaded NPs (Cur-NPs) of small size were obtained from the copolymer’s self-assembling aided by thin-film hydration with effective encapsulation. 10 Our results demonstrated that Cur-NPs can significantly raise dissolution ratio of curcumins in water, providing a proper sustained-release characteristic for curcumin in vitro, suggesting that the Cur-NP is an appropriate candidate for the continuous delivery of curcumin. In the current study, we further evaluated the anti-atherosclerotic function of this Cur-NPs in apolipoprotein E −/− mice (apoE −/− mice).…”
Section: Introductionmentioning
confidence: 56%
“…Moreover, the release behavior of curcumin from the nanoparticle has been investigated in our previous studies. 10 The release results demonstrated that the release of curcumin from control solution was much faster, about 87% of curcumin was released in 20 h. In contrast, the Cur-NPs showed a sustained-release property and the accumulative release percentage at 60 h was about 81%. These results suggested that Cur-NPs would have a prospective clinical application as a new injectable dosage form.…”
Section: Resultsmentioning
confidence: 92%
“…These results suggested that LNC could be used for the delivery of traditional medicines to cancer cells. The methoxy poly(ethylene glycol)-b-poly(ε-caprolactone) (mPEG-PCL) micelles could extend the plasma concentration and delay the clearance of curcumin 38. The bioavailability and t 1/2 of curcumin were greatly improved when loaded with Poly (D, L-lactic acid)-glycerol (PDLLA-G) when compared with free curcumin 39…”
Section: Resultsmentioning
confidence: 99%
“…In vitro ETP release from FA-ETP-NLCs and ETP-NLCs was assessed by the dialysis method (Song et al, 2015). FA-ETPNLCs and ETP-NLCs were positioned in the dialysis bag separately.…”
Section: In Vitro Drug Releasementioning
confidence: 99%